Analysis of Determining Target Accuracy of Rocket Launchers on Xbee-Pro based Wheeled Robots to Realize the Development of Technology on the Military Field - Anggara Trisna Nugraha; Dadang Priyambodo (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2020)
At this time the rocket launcher is still controlled by humans who utilize technology using a PC and a servo motor as a control device to determine the accuracy at the shooting angle, in designing this robot complete components are needed so that the robot can work automatically according to the input given, the rocket launcher robot controlled automatically by communication from the PC after which the command is forwarded to the microcontroller using a USB TTL cable and sent to the Xbee-pro sender circuit then transmitted and received by the Xbee-pro receiver then transmitted to the microcontroller and processed to the control system on the launcher a rocket in the form of a servo motor and a relay as a component in the firing of the rocket launcher. Based on the test results, the robot has been able to direct the rocket launcher at a predetermined angle and has been able to carry out firing actions on each rocket starting from manual rockets, double rockets, triple rockets and full rockets with a success rate of up to 80%.